Detection of HLA Antibodies in Organ Transplant Recipients – Triumphs and Challenges of the Solid Phase Bead Assay - Tait, Brian D. (Frontiers in Immunology, 2016)
This review outlines the development of HLA antibody detection assays and their use in organ transplantation in both antibody screening and crossmatching. The development of sensitive solid phase assays such as the ELISA technique, and in particular the bead based technology has revolutionised this field over the last 10 to 15 years. This revolution however has created a new paradigm in clinical decision making with respect to the detection of low level pre-transplant HLA sensitisation and its clinical relevance. The relative sensitivities of the assays used are discussed and the relevance of conflicting inter-assay results. Each assay has its advantages and disadvantages and these are discussed in detail. Over the last decade the bead based assay utilising the Luminex® fluorocytometer instrument has become established as the “gold standard” for HLA antibody testing. However there are still unresolved issues surrounding this technique, such as the presence of denatured HLA molecules on the beads which reveal cryptic epitopes and the issue of appropriate fluorescence cut off values for positivity. The assay has been modified to detect complement binding (CB) in addition to non-complement binding (NCB) HLA antibodies although the clinical relevance of the CB and NCB IgG isotypes is not fully resolved. The increase sensitivity of the Luminex® bead assay over the CDC crossmatch has permitted the concept of the “virtual crossmatch” whereby the crossmatch is predicted to a high degree of accuracy based on the HLA antibody specificities detected by the solid phase assay. Dialogue between clinicians and laboratory staff on an individual patient basis is essential for correct clinical decision making based on HLA antibody results obtained by the various techniques.